Psychological distress experienced by nurses amid the fifth wave of the COVID-19 pandemic in Hong Kong: A qualitative study - Cheung, Ankie Tan; Ho, Laurie Long Kwan; Li, William Ho Cheung; Chung, Joyce Oi Kwan; Smith, Graeme D. (Frontiers in Public Health, 2023)
Introduction The fifth wave of COVID-19 has significantly overburdened the health care system in Hong Kong. Health care professionals, particularly nurses continue to experience significant levels of psychological distress when tackling this ongoing outbreak. Yet, no study has explored the psychological experiences of nurses during the most recent outbreak of the highly transmissible Omicron variant in Hong Kong. The aim of this qualitative study was to explore the psychological distress experienced by nurses during the fifth wave of the COVID-19 pandemic in Hong Kong. Methods Twenty-two nurses (14 female and 8 male nurses; average age, 36.7 ± 8.5 years) were recruited to attend the one-to-one semi-structured telephone interviews from June to July, 2022. Data were analyzed using thematic analysis. Results Four main themes emerged from the interview: (1) Intense fear, worry, and anxiety; (2) Feeling worn out and psychologically distress; (3) Impact on psychosocial and physical health; and (4) Limited options to cope with psychological distress during the difficult times. Discussion Our study findings may provide concerned stakeholders with useful insights into reducing the psychological distress experienced by nurses in Hong Kong. Offering psychological support is of paramount importance to address the unmet psychological needs of nurses and reduce their psychological distress during the pandemic, particularly when they are working under high levels of workplace stress.